Pengaruh Asam Humat pada Media Tanam Zeolit terhadap Pertumbuhan dan Kandungan Vitamin C Sawi Hijau (Brassica juncea) - Istiq Fauziah; Elly Proklamasiningsih; Iman Budisantoso (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2019)
Green mustard (Brassica juncea) as one of the commonly consumed vegetables and acts as one of the main sources of C vitamin in addition to fruits. C vitamin is needed for the body because it has antioxidant. Humic acid is a component of organic acid soil which can increase the production of food crops and plantations. Zeolites have a hollow structure that allows use as a carrier of humic acid. Aside from being a career zeolite which is applied with humic acid can act as an ameliorant material, this is useful in increasing crop production. The objectives of this study are to determine the effect of humic acid with zeolite planting media on the growth and content of C vitamin on green mustard plants and determine the concentration of humic acid which most influences the growth and content of C vitamin in green mustard plants. The research was conducted at the Laboratory of Plant Physiology and Green House, Faculty of Biology, Jenderal Soedirman University, Purwokerto using an experimental method. The study was carried out from January to February 2019 using an experimental design namely Completely Randomized Design (CRD). The parameters were the number of leaves, wet weight and dry weight of roots, stems, leaves and C vitamin. The data obtained will be analyzed by analysis of variance at the confidence level of 95% and 99%, if the results are significantly different then continued with LSD at 95%. The results showed that application of humic acid in zeolite planting media had a very significant effect on growth and C vitamin content of green mustard greens. Humic acid with a concentration of 4 g.kg-1 is the most efficient concentration in increasing growth and C vitamin content of green mustard greens.